Shoah - Vice, Sue 1961- (BFI film classics, 2011)
Lanzmann as film-maker -- Documentary or 'fiction of the real'? -- Archive footage -- 'Reincarnating' the past -- Mise en scène -- Lanzmann as interviewer -- Poland: the ethics of filming -- Testimony -- Appendix: overview of Shoah